Inhibitory Effects of Combination of Lycopene and Genistein on 7,12-Dimethyl Benz(a)anthracene-Induced Breast Cancer in Rats - Şahin, Kazım; Tuzcu, Mehmet; Şahin, Nurhan; Akdemir, Fatih; Ozercan, Ibrahim; Bayraktar, Soley; Küçük, Ömer (Routledge Journals, Taylor & Francis Ltd, 2011)
Breast cancer is one of the most common cancers in women. Carotenoids and soy isoflavones have been postulated to have breast cancer preventive effects. We investigated the potential preventive effects of lycopene and genistein, alone and in combination, on breast cancer development in female Wistar rats treated with 7,12-dimethylbenz[a]anthracene (DMBA), a carcinogen known to induce breast tumors. Mammary carcinogenesis was initiated by a single, oral gavage of DMBA (80 mg/kg body weight) at 55 days of animal age. Fifty female Wistar rats were divided into 5 experimental groups having 10 animals per group: Group 1 (normal control), Group 2 (DMBA control), Group 3 (DMBA + lycopene), Group 4 (DMBA + genistein), and Group 5 (DMBA + lycopene and genistein). Rats were fed either lycopene (20 mg /kg bw) or genistein (2 mg /kg bw) by oral gavage (3 times per week) starting 2 wk prior to DMBA injection. Treatment was continued for 20 wk. Rats treated with DMBA developed mammary tumors with 100% tumor incidence during the 20-wk study. Inhibition of mammary cancer incidence by lycopene (70%), genistein (60%) and their combination (40%) was observed. Tumor weight decreased by 48%, 61%, and 67%, and mean tumor volume decreased by 18%, 35%, and 65% with lycopene, genistein, and lycopene + genistein, respectively (P < 0.01 for the combination). The proportions of adenocarcinoma masses decreased with lycopene and genistein combination (P < 0.05). Administration of lycopene and genistein combination suppressed breast cancer development and was associated with a decrease in MDA, 8-isoprostane, and 8-OhdG levels and with an increase in serum lycopene and genistein levels. Animals administered DMBA developed breast cancer, which was associated with increased expression of Bcl-2 and decreased expression of Bax, caspase 3, and caspase 9 in mammary tissues. Administration of genistein and lycopene in combination was more effective in inhibiting DMBA-induced breast tumors and modulating the expression of apoptosis associated proteins than the administration of each agent alone. Our results suggest that lycopene and genistein are potent antioxidants and, when given in combination, offer maximum protection against DMBA-induced mammary carcinogenesis.
Keywords: Xenobiotic-Metabolizing Enzymes; Vivo Antioxidant Properties; Soy Isoflavone Genistein; Bcl-2 Family-Members; Oxidative Stress; in-Vitro; Estrogen-Receptor; Dietary Lycopene; Tomato Carotenoids; Mammary-Cancer